R.A. Kartini’s Letters: The Emergence of the Subaltern? - Eta Farmacelia Nurulhady (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
This study investigates R.A. Kartini’s letters to find out how her published letters represent the emerging of the subaltern voice. Using postcolonial criticism, this study scrutinizes ways in which Kartini’s letters show traces of the Dutch colonialism’s ideology and interprets the letters as challenging the Dutch’s purposes and hegemony. Focusing on Kartini’s concerns regarding colonized women’s position in society and their education, Kartini’s letters show her mimicry and ambivalence of her identity as a colonized subject. The publication of her letters enable her subaltern voice to be heard.